2001
DOI: 10.1177/03635465010290061101
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Effect of Varying Suture Pitch in Tendon Graft Fixation

Abstract: The purpose of this study was to biomechanically assess the effect of varying suture pitch on the holding power of the Krackow suture technique for tendon graft fixation. Seven pairs of rabbit Achilles tendons were sutured with single No. 5 Ti-Cron suture using the Krackow technique. One tendon from each pair was sutured using a 0.5-cm suture pitch (half-pitch group) while the contralateral tendon from each pair was sutured with a 1.0-cm suture pitch (one-pitch group). The tendons were loaded to failure using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
2
31
1
Order By: Relevance
“…These results were expected because several studies have reported similar findings. 8,14,17,18,20 The test configuration in the present study was adapted from that of Su et al, 14 in which securing sutures over the bar with 5-throw square knots probably contributed to stress risers in the knot, whereas friction of the suture under the bar resulted in suture breakage at the knot level, which is similar to previous studies. Therefore, it can be assumed that the peak load to failure of the suture-tendon construct may actually exceed the breaking strain of the suture; thus graft-holding strength of the 3 suture techniques could not be compared with this testing condition because suture breakage was the mode of failure.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results were expected because several studies have reported similar findings. 8,14,17,18,20 The test configuration in the present study was adapted from that of Su et al, 14 in which securing sutures over the bar with 5-throw square knots probably contributed to stress risers in the knot, whereas friction of the suture under the bar resulted in suture breakage at the knot level, which is similar to previous studies. Therefore, it can be assumed that the peak load to failure of the suture-tendon construct may actually exceed the breaking strain of the suture; thus graft-holding strength of the 3 suture techniques could not be compared with this testing condition because suture breakage was the mode of failure.…”
Section: Discussionsupporting
confidence: 75%
“…8 These ligament reconstruction procedures often use 2 sets of free sutures attached to each end of the graft limb, which are then passed through the bone tunnel and tied over the bone bridge to secure the graft completely docked within the tunnel. Elongation of the graft construct under loading, which may lead to clinical failure, has been of significant concern.…”
mentioning
confidence: 99%
“…The Krackow stitch was able to prevent suture slippage by the locking mechanism, and there was no significant effect of the number of throws on the holding strength. Additional suture throws may increase the risk of eventually lengthening through slippage 12,17 ; fewer throws may provide less potential for elongation caused by suture slippage. The results of this study suggest that the Krackow stitch is usually preferable for suturing tendons than a whipstitch and a baseball stitch.…”
Section: C-fmentioning
confidence: 99%
“…They reported a failure strength of 392 N, which is twice as strong as staple fixation into bone, when 2 Krackow sutures were placed into each end of the bovine medial collateral ligament. 14 Jassem et al, 12 in an in vitro study using rabbit Achilles tendon, demonstrated an increasing stiffness of 1-cm pitch using the Krackow stitch compared with 0.5-cm pitch, whereas failure loads and displacements were not different between the 2 groups. However, there are no data in the literature concerning biomechanical comparison of various suture techniques and suture throws when preparing hamstring tendon autografts.…”
mentioning
confidence: 96%
“…Minimizing gap formation and elongation of the suture-soft tissue repair or reconstruction is critical in creating and maintaining a functional fixation construct. 5 Several different suture configurations for tendon repair and reconstruction are widely implemented based on surgeon preference. Although the guidelines for y selection of suture technique are not strictly defined, commonly preferred suture techniques are the Krackow locking stitch and the nonlocking whipstitch.…”
mentioning
confidence: 99%